Women’s Vulnerability in Bean Value Chain Development at the Maendeleo Innovation Platform, Eastern DRC - Kalibwani, R.M.; Nyamwaro, S.O.; Wimba, B.; Kakuru, M.; Tenywa, M.M.; Mugabo, J.; Buruchara, R.A. (African Journal of Rural Development, 2018)
Value chain development in post conflict countries should not only deal with the technical issues of the value chain, but with women’s gender needs, and even more critically understand and address their vulnerabilities. The aim of this study was to investigate the vulnerabilities of women involved in a bean value chain development intervention at the Maendeloe Innovation Platform in Eastern DRC. Specifically, the paper first discusses the roles of women and men in the value chain, what production resources and benefits they access and control, the role of the IP as a vehicle for women’s empowerment, and identifies women’s gender needs. Secondly, the paper identifies women’s vulnerabilities, and the capacities that the IP could build on, to support their participation in bean value chain development. Using gender analysis tools, the study shows that in addition to the lack of control of productive resources, household assets and the benefits of their labour, women have been traumatized by the rampant sexual violation and gender-based violence in the region. The innovation platform should consider including legal, mental health and psychosocial counselling service providers as stakeholders in its activities to develop the bean value chain.
Keywords: Innovation platform; Value chain; Vulnerability; Women